2001
DOI: 10.1097/00001665-200111000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Techniques in the Treatment of Pleomorphic Adenoma of the Parotid Gland: Our Experience and Review of Literature

Abstract: This paper presents a retrospective study carried out on a sample of 100 patients affected by pleomorphic adenoma of the parotid gland and treated at the Department of Maxillofacial Surgery at the University of Rome "La Sapienza" between January 1, 1989 and December 31, 1997. For the diagnosis of this neoformation, cytological tests were performed on material taken from the neoformation using fine needle aspiration and ultrasound scan. In some selected cases, a CT examination of the head and neck with medium c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
4

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 19 publications
2
13
0
4
Order By: Relevance
“…Five studies (Martis, 1983;Corcione and Califano, 1990;Federspil et al, 1994;Van Hee et al, 1996;Marchesi et al, 2006) were judged to be at high risk of bias and 8 studies (Debets and Munting, 1992;Laskawi et al, 1996;Leverstein et al, 1997;Rehberg et al, 1998;Valentini et al, 2001;Guntinas-Lichius et al, 2004;Zernial et al, 2007;Riad et al, 2011) were considered at moderate risk of bias.…”
Section: Quality Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Five studies (Martis, 1983;Corcione and Califano, 1990;Federspil et al, 1994;Van Hee et al, 1996;Marchesi et al, 2006) were judged to be at high risk of bias and 8 studies (Debets and Munting, 1992;Laskawi et al, 1996;Leverstein et al, 1997;Rehberg et al, 1998;Valentini et al, 2001;Guntinas-Lichius et al, 2004;Zernial et al, 2007;Riad et al, 2011) were considered at moderate risk of bias.…”
Section: Quality Assessmentmentioning
confidence: 99%
“…A total of 1291 patients were enrolled in 8 studies (Corcione and Califano, 1990;Laskawi et al, 1996;Leverstein et al, 1997;Rehberg et al, 1998;Valentini et al, 2001;Guntinas-Lichius et al, 2004;Marchesi et al, 2006;Zernial et al, 2007). The total number of patients in the SP group was 1003 and in the TCP group was 288.…”
Section: Facial Nerve Paresismentioning
confidence: 99%
“…Ward (12), Woods (13), Aljamo (14), Mehle (9), and Valentini (15) have reported that superficial parotidectomy and/or total parotidectomy with preservation of the facial nerve is the gold standard for excision of parotid tumors. However, in their studies, they report a number of post-operative complications related to facial nerve injury.…”
Section: Discussionmentioning
confidence: 99%
“…In our case, recurrences occurred 7 and 14 years after the initial surgical treatment. The treatment of recurrences is complicated and technically difficult because of the fibrosis, adhesions, and changes in anatomic references that increase the risk of facial nerve lesions (14).…”
Section: Discussionmentioning
confidence: 99%